2023
DOI: 10.11591/ijphs.v12i1.21982
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety status of junior archers in COVID-19 during training isolation period towards the shooting performance

Abstract: <p>Studies have indicated that the COVID-19 pandemic has had miserable effects on athlete performance due to the movement control order (MCO) announced by the Malaysia Government. Dealing with self-training without the coach's guidance leads the archers to lose concentration, diminished self-confidence, and elevated anxiety levels. These factors contribute to inconsistent shooting performance. This study attempted to identify the archer's anxiety status during the training isolation period on the shootin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…There are studies suggesting that anxiety may have both a fa cilitative and a negative role in sportive performance [45,46]. A study showing that increased levels of anx iety during the Covid19 pandemic caused inconsistent shooting performance in archers suggests that anxiety negatively affects performance in archery, an indi vidual sport [47]. Martens et al reported anxiety to have two components when it comes to sports, namely cognitive and somatic, in which the cognitive compo nent involves negative expectations related to success (negative linear relationship), while the somatic com ponent is a physiological and affective component that is directly related to an autonomic stimulus, with both low and high levels affecting sportive performance negatively.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies suggesting that anxiety may have both a fa cilitative and a negative role in sportive performance [45,46]. A study showing that increased levels of anx iety during the Covid19 pandemic caused inconsistent shooting performance in archers suggests that anxiety negatively affects performance in archery, an indi vidual sport [47]. Martens et al reported anxiety to have two components when it comes to sports, namely cognitive and somatic, in which the cognitive compo nent involves negative expectations related to success (negative linear relationship), while the somatic com ponent is a physiological and affective component that is directly related to an autonomic stimulus, with both low and high levels affecting sportive performance negatively.…”
Section: Discussionmentioning
confidence: 99%